Botulinum Injection and Sphincterotomy for Management of Anal Fissure in Terms of Healing of Anal Fissure: A Randomized Controlled Trial - Rashid Minhas, Ali Akbar, Muhammad Mushtaq, Rashid Mehmood, Humayun Siiddique, Manzar Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the efficacy of botulinum injection with lateral internal sphincterotomydone for management of anal fissure in terms of healing of anal fissure Study design: Randomized controlled trail Setting and duration: Department of General Surgery, K.E. Medical University, Lahore from April, 2019 to Oct, 2019 Methodology: All 350(175 cases in each group) cases meeting inclusion criteria were enrolled through department of Surgery KEMU. Patients were randomly allocated in two groups, group A and B by Lottery method. Patients in group ‘A’ received treatment with 0.5 ml (20 units) Botulinum toxin injection on each side of anal fissure in the internal anal sphincters under direct vision and digital examination at 3 or 9 o’clock position in lithotomy position under strict aseptic measures by single expert surgeon having at least five years’ post fellowship experience. Patients in group ‘B’ underwent lateral internal anal sphincterotomy under general anesthesia by single expert surgeon also having at least five years’ post fellowship experience. Patients were discharged on 1st post operation day on oral antibiotics, analgesics, stool softeners and were advised sitz bath. In both groups, patients were followed up for 2 months. Results: The mean age of all patients was 43.09 ± 10.68 years while the mean age in Group-A was 43.17±10.32 years and in Group-B was 43.02±11.06 years. The efficacy in Group-A was seen in 158(90.3%) while the efficacy was seen in 114(65.1%) of Group-B, the efficacy of treatment was higher in group-A when compared with Group-B, p-value < 0.001. Conclusion: Botulinum toxin injection for the treatment of anal fissure has yielded higher rates of healing than lateral internal sphincterotomy. This suggests that botulinum injection could provide temporary relief from sphincter spasm, allowing for faster fissure healing and improved quality of life, with fewer risks of complications. Keywords: Sphincterotomy, anal fissure, healing of anal fissure, rectal pain, anal pain, anal surgery